Monotonicity of Solution Sets for Parameterized Optimization Problems - Leslie M. Marx (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
This paper uses results of lattice theory, convex analysis, and nonsmooth analysis to establish conditions for the existence of pure-strategy Nash equilibria when payoff functions are continuous but not quasi-concave. A class of economic games for which this theory is important is given.
Keywords: 330